(untitled) (Biological Sciences - PJSIR, 1999)
The improvement of yield stability in spring wheat is a major plant breeding objective. The yield of ten spring wheat genotypes were determined for three seasons (1992-1994) at nine sites in Sindh province. The genotypes environments interaction was highly significant (P O.OI). Heterogeneity between regression for genotypes (P O.05) and deviation from regression (P:::;O.OI)were significant. Genotype SI88123 had the highest mean yield over environment and was generally adapted to all the environments. WRS-OI, SI88155 and SI88231 had lower mean yield over environments.